Functional Heterogeneity of Reelin in the Oral Squamous Cell Carcinoma Microenvironment - Zhang, Xinwen; Fu, Yong; Ding, Zhuang; Zhu, Nisha; Zhao, Mengxiang; Song, Yuxian; Huang, Xiaofeng; Chen, Sheng; Yang, Yan; Zhang, Caihong; Hu, Qingang; Ni, Yanhong; et al. (Frontiers in Oncology, 2021)
Background Reelin, an extracellular glycoprotein, is expressed on neuronal cells and participates in neuronal migration during brain development. Recently, Reelin also has a vital role in carcinogenesis. However, its role in oral squamous cell carcinoma (OSCC) remains to be explored. The purpose of this study was to explore the roles of Reelin in OSCC. Methods The expression of Reelin in cancer-associated fibroblasts (ReelinCAF) and tumor cells (ReelinTC) was analyzed by the Gene Expression Omnibus (GEO) database. Immunohistochemistry (IHC) was used to detect the spatial pattern of Reelin in 75 OSCCs. The diagnostic and prognostic values of Reelin were evaluated and also verified by The Cancer Genome Atlas (TCGA) database. Primary CAFs from 13 OSCC patients were isolated to confirm Reelin expression. Thirty-nine OSCC peripheral blood samples were used to analyze the change of immunocytes based on Reelin levels by flow cytometry. The relationship between Reelin and tumor immune microenvironment in head and neck squamous cell carcinoma (HNSCC) tissues was determined by TISIDB and the Tumor Immune Estimation Resource (TIMER) database. Results In breast cancer, pancreatic cancer and rectal cancer, Reelin in CAFs was significantly upregulated compared with Reelin in TCs. The IHC results in OSCC also showed that Reelin levels were higher in CAFs. Upregulated ReelinTC was related to a decreased pN stage and distant metastasis. Strikingly, patients with enhanced ReelinCAF had a high risk of lymph node metastasis, poor worst pattern of invasion (WPOI), and distant metastasis, but showed comparable Ki-67 level in all OSCC patients, resulting in shorter overall survival (OS) and disease-specific survival (DSS). Unexpectedly, Reelin in tumor-infiltrating lymphocytes (ReelinTIL) was correlated with postoperative relapse. Patients with high ReelinTIL, but not ReelinTC and ReelinCAF, had poor cytotoxicity of CD8+ T cells and higher ratio of CD4/CD8 in peripheral blood. However, Reelin was positively associated with tissue-resident B cells and NK cells in the tumor microenvironment. Conclusion Reelin has a versatile function in distinct cell types during the development of OSCC via governing tumor cell and stroma microenvironment.